2021
DOI: 10.46582/jsrm.1701003
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1, in a Conducive Milieu with Wnt/BMP/Retinoic Acid, Prolongs the Epicardial-Mediated Cardiac Regeneration Capacity of Neonatal Heart Explants

Abstract: Rationale: Cardiac sympathetic nerves are required for endogenous repair of the mammalian neonatal heart in vivo, but the underlying mechanism is unclear. Objective: We tested the hypothesis that a combination of cardiac developmental growth factors Wnt3a, BMP4 and Neuregulin (NRG-1), compensate for denervation and support cardiac regeneration in explanted neonatal mammalian hearts. Methods and Results: Hearts from 2-day old neonatal mice were harvested, lesioned at the apex and grown ex vivo for 21 days under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…VEGF mRNA has been administrated to patients via direct intramyocardial injection, showing that it may be safe for introducing genetic material to the cardiac muscle [ 178 ]. Nrg1 sustains the epicardial-mediated cardiac regeneration capacity of neonatal heart explants [ 179 ]. Oxytocin also activates epicardial cells and promotes heart regeneration after cardiac injury [ 180 ].…”
Section: Approaches and Challenges For Heart Regenerationmentioning
confidence: 99%
“…VEGF mRNA has been administrated to patients via direct intramyocardial injection, showing that it may be safe for introducing genetic material to the cardiac muscle [ 178 ]. Nrg1 sustains the epicardial-mediated cardiac regeneration capacity of neonatal heart explants [ 179 ]. Oxytocin also activates epicardial cells and promotes heart regeneration after cardiac injury [ 180 ].…”
Section: Approaches and Challenges For Heart Regenerationmentioning
confidence: 99%
“…They observed that the Tp53 network is transiently suppressed during zebrafish heart regeneration, increasing CMs proliferation, indicating that this molecular pathway is directly related to innate regeneration in zebrafish [ 141 ]. In addition, zebrafish ex vivo experiments performed by Arora et al [ 142 ] demonstrated that the combination of Wnt family member 3 (Wnt3), Bone morphogenetic protein 4 (BMP4) and Nrg1 has a regenerative effect in damaged neonatal hearts in culture. The combination of these growth factors promotes cardiac repair via epicardial cell activation, their proliferation and migration to the injury site, followed by CMs recruitment [ 142 ] ( Figure 3 A).…”
Section: Reactivation Of Cell Proliferation For Heart Repairmentioning
confidence: 99%
“…In addition, zebrafish ex vivo experiments performed by Arora et al [ 142 ] demonstrated that the combination of Wnt family member 3 (Wnt3), Bone morphogenetic protein 4 (BMP4) and Nrg1 has a regenerative effect in damaged neonatal hearts in culture. The combination of these growth factors promotes cardiac repair via epicardial cell activation, their proliferation and migration to the injury site, followed by CMs recruitment [ 142 ] ( Figure 3 A). Finally, Nrg1 regulates CMs proliferation through the activation of the Ras/Mapk pathway, which is controlled by feedback attenuator Dual specificity phosphatase 6 (Dusp6), an ERK phosphatase [ 143 ] ( Figure 3 A).…”
Section: Reactivation Of Cell Proliferation For Heart Repairmentioning
confidence: 99%
“…As a cardiac regeneration growth factor, NRG1 has attracted the attention of cardiovascular medicine. NRG1 has been shown to not only stimulate cardiomyocyte proliferation ( Zhao et al, 1998 ; Bersell et al, 2009 ; D'Uva et al, 2015 ), but also act within angiogenesis, extracellular matrix remodeling, cardiomyocyte proliferation, stem-cell recruitment, and others, that improve cardiac function ( Mendes-Ferreira et al, 2016 ; Rebouças et al, 2016 ; Arora et al, 2021 ). Together, these mechanisms promote myocardial repair and improvement of the cardiac function, that providing a novel molecular strategy targeting at regenerating the injured myocardium.…”
Section: Introductionmentioning
confidence: 99%